New U.S. tariff policies: What’s at stake for sub-Saharan Africa? - Piñeiro, Valeria; Gianatiempo, Juan Pablo; Traoré, Fousseini; Glauber, Joseph W. (International Food Policy Research Institute, 2025)
Current U.S. trade policies—though primarily focused on major global players including China, the European Union, and North American partners Canada and Mexico—also have economic consequences for smaller countries and regions around the world. In sub-Saharan Africa (SSA), these impacts will be felt both directly, through newly imposed tariffs, and indirectly, as collateral damage in a potential trade war between the world’s largest economies.